Influence of the methanol extract and fractions of Smilax brasiliensis Sprengel on development in vitro of Nicotiana tabacum and Alllium cepa (Research, Society and Development, 2021)
Smilax brasiliensis (Smilacaceae) is a native Brazilian plant found in the Cerrado biome and commonly used in folk   medicine. The aim of this study was to evaluate the influence of the methanol extract and fractions from S. brasiliensis leaves on development in vitro of Nicotiana tabacum (tobacco) and Allium cepa (onion) seeds. In vitro germination protocol of onion seeds was established. Tobacco and onion seeds were placed to germinate on basal medium added of extract or fractions of S. brasiliensis leaves and dichlorophenoxyacetic acid (2,4-D), 6-benzylaminopurine (BAP) and gibberellic acid (GA) at different concentrations in the presence of light. The germination ranged from 40 to 100% for tobacco and from 60 to 100% for onion seeds. The results indicated that the extract and fractions promoted higher growth than 2,4-D and GA when analyzed number of nodes, leaves, root and root size for germinated tobacco seeds, and higher growth when analyzed number roots and stem size for onion seeds. Regarding BAP, the extract and fractions inhibited leaf growth, root and root size of tobacco seeds. Further studies are needed to evaluate the possible use of the methanol extract and fractions from S. brasiliensis leaves as natural sources of hormones and/or bioherbicides.